„Chwylowizm” Mykoły Chwylowego: szkoła literacka czy „zboczenie” ideologiczne? - Nowacki, Albert (Studia Ukrainica Posnaniensia, 2023)
The works of Mykola Khvylovyi – one of the most recognizable writers of the 1920s – has many blank spots, which is why it is still the subject of scientific research in literary studies, political science and history. There is no doubt that the ideas of this Ukrainian writer significantly influenced not only the course of Ukrainian literary discussion but also the shape of contemporary Ukrainian literature. The aim of this article is to attempt to examine the phenomenon known as “khvylovism” and to prove that it is a phenomenon artificially created by the ideologists of the communist party in the 1920s. The author pays particular attention to the fact that “khvylovism” cannot be treated as a system of the writer’s political views but as a concept for the development of independent Ukrainian literature